Accuracy of segmented measurement of axial length in ultra-high myopia filled with silicone oil using immersion B-scan ultrasonography - Qing-Hua Yang; Hong-Tao Zhang; Xiao-Qi Li; Bing Chen; Zhao-Hui Li; Yi-Fei Huang; Xin Jin; Ying Zhang; Li-Qiang Wang (International Journal of Ophthalmology, 2022)
AIM: To evaluate the accuracy of segmented measurement of axial length (AL) in high myopia filled with silicone oil by immersion B-scan ultrasonography (immersion B-scan). METHODS: From June 2016 to June 2020, a total of 67 ultra-high myopia inpatients (67 eyes) who underwent silicone oil removal combined with cataract extraction and intraocular lens (IOL) implantation were retrospectively enrolled. The preoperative axial length (AL) of 31 patients with severe cataract were segmented measured using immersion B-scan (B-scan group) and another 36 patients with mild or moderate cataract were measured using IOLMaster 500 (IOLMaster group). The post-operative ALs in two groups were both measured using IOLMaster 500. The IOL power was calculated with Haigis formula. The differences in ALs between pre- and post-surgery, as well as the postoperative refractive spherical equivalent, absolute refractive error, the prediction deviation of postoperative refraction and best corrected visual acuity (BCVA) were compared. RESULTS: The pre- and post-operative ALs were 30.46±1.63 mm (range 28.09-33.51 mm) and 30.42±1.70 mm (range 28.03-33.90 mm) in B-scan group (t=0.644, P=0.542) and 30.51±1.21 mm (range 28.03-33.90 mm) and 30.43±1.27mm (range 28.54-33.50 mm) in IOLMaster group (t=1.843, P=0.074), respectively. Three months after surgery, BCVA were 0.45±0.13 (range 0.3-0.9) and 0.44±0.20 (range 0.2-1.0) in B-scan and IOLMaster group respectively (t=0.086, P=0.932). There was no significant difference of the postoperative spherical equivalent (-3.11±0.65 D vs -3.21±0.51 D, t=0.671, P=0.505) and the absolute refractive error (0.589±0.340 vs 0.470±0.245 D, t=1.615, P=0.112) between two groups. In B-scan group, absolute refractive error within ±0.50 D was found in 18 eyes (58.1%), within ±1.00 D in 26 eyes (83.9%), and within ±1.50 D in 31 eyes (100%). In IOLMaster group, absolute refractive error within ±0.50 D was found in 23 eyes (63.9%), within ±1.00 D in 34 eyes (94.4%), and within ±1.50 D in 36 eyes (Z=0.757, P=0.449). CONCLUSION: The segmented measurement of ALs by immersion B-scan shows comparable measurement accuracy with that of IOLMaster 500 in ultra-high myopia patients with severe cataract secondary to silicone oil filling and can obtain an ideal postoperative refractive state.